ChemInform Abstract: Synthesis of 1, 3‐Aminonaphthols by Diastereoselective Betti‐Type Aminoalkylation of Dihydroxy Naphthalenes; Diastereoselectivity, Absolute Configuration, and Application. Issue 20 (20th May 2014) - Marinova, Maya; Kostova, Kalina; Tzvetkova, Pavleta; Tavlinova‐Kirilova, Maya; Chimov, Angel; Nikolova, Rosica; Shivachev, Boris; Dimitrov, Vladimir
Abstract Solventless Betti‐type condensation of 2, 6‐dihydroxynaphthalene with (S)‐phenethylamine with aromatic aldehydes is investigated together with the analogous reactions of 2‐hydroxynaphthalene.